Proceso atención de enfermería en paciente femenina de 48 años con diagnóstico de leiomioma del útero. - Moreira Morejón, Didi Jeampool (2024)
Uterine leiomyomas or fibroids are solid, benign tumors of the uterine muscle, which vary in shape, location, and size, affecting the uterine body. They are classified according to their location and can be intramural, submucosal, or subserosal. The incidence of uterine fibroids in Ecuador is estimated to be between 30% and 50% of women, and this percentage increases to up to 70% in women of childbearing age. The clinical case shows that this condition is a real and potential problem for women over 35 years old, affecting not only their quality of life but also their emotional well-being. This research work allowed me to gain new knowledge about this disease and the appropriate and necessary nursing care required. By applying the nursing care process, we aim for the patient's swift recovery based on their treatment, helping not only with their physical or biological aspect but also providing emotional support.